IMPLEMENTASI GREEN MARKETING DAN DIGITAL MARKETING PADA UMKM BINAAN TELKOM COMMUNITY DEVELOPMENT CENTER SURABAYA - Sekar Widyasari Putri; Ahmad Wali Satria Bahari Johan; Riza Akhsani Setyo Prayoga; Jenny Ghifrina; M. Ghouzul A’dhom; Vagnes Angela (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The COVID-19 pandemic has had a significant impact on the industry, such as layoffs. Employees affected by layoffs fulfill their daily needs by becoming MSME actors in the hope of becoming a source of income. Telkom CDC (Community Development Center) is a division of PT Telkom Indonesia as a distributor of CSR (Corporate Social Responsibility) funds for MSMEs in the Surabaya area. Based on an interview with the Telkom CDC Manager as an MSME supervisor, he provided information about the problem of soft loan funds being channeled to MSME actors who did not return, because their business was not yet profitable. This is because business actors do not evaluate and improve their business. In addition, during the pandemic, training for MSME actors was also very limited so MSME actors' knowledge, especially on effective marketing, was also lacking. They cannot keep up with the digitalization and packaging trends that attract consumer interest and trust in the products offered. Therefore, we try to provide solutions from the marketing side by providing digital marketing training and the application of green marketing in the form of attractive environmentally friendly packaging.